Tuning and understanding the phase interface of TiO2 nanoparticles for more efficient lithium ion storage. Issue 30 (14th July 2015) - Wang, Rui; Xue, Xuyan; Lu, Wencai; Liu, Hongwei; Lai, Chao; Xi, Kai; Che, Yanke; Liu, Jingquan; Guo, Shaojun; Yang, Dongjiang
Abstract : We demonstrate that mixed-phase anatase–TiO2 (B) nanoparticles can provide an interesting interphase interface with atomic-level contact for achieving more efficient Li ion storage with high capacity and cycle life. Abstract : We demonstrate that mixed-phase anatase–TiO2 (B) nanoparticles can provide an interesting interphase interface with atomic-level contact for achieving more efficient Li ion storage with high capacity and cycle life. A novel lithium storage mode – "interfacial charge storage in allomorphs" (ICSA) – plays an important role in enhancing Li ion storage.